TANGGUNG JAWAB NOTARIS ATAS PEMBUATAN PERJANJIAN PERKAWINAN BERDASARKAN PUTUSAN MK NO. 69/PUU-XIII/2015 DI KABUPATEN TABANAN - Komang Febrinayanti Dantes; I Gusti Ayu Apsari Hadi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This study aims to found the responsibility of Notary when made prenuptial or postnuptial agreement based on Constitutional Court Decision Nr. 69/PUU-XII/2015. The decision of Constitutional Court has changed competency a Notary in making prenuptial aggrement. This study is legal empirical with uses qualitative description and sistematic. The results showed there is different prenuptial agrement that made by Notary and postnuptial agrement issued by Constitutional Court Decision Nr. 69/PUU-XIII/2015. Constitutional Court Decision N0. 69/PUU-XIII/2015 which contains clauses that the agreement is made after the marriage has taken place before a Notary. In addition, the responsibility of the Notary to the marriage agreement deed based on the Constitutional Court's decision must be ensured that the parties who make the marriage agreement after the marriage is not committing an unlawful act which then affects the assets of the parties.